Global Mild Solutions and Long Time Decay of 3D Incompressible MHD Equations (Journal of Partial Differential Equations, 2020)
We prove the global existence of a unique mild solutions to the incompressible MHD equations when the initial data are less than the viscosity coefficients in anew critical space introduced by Lei and Lin [1]. Moreover, we prove that solutionsdecay to zero as time goes to infinity.
Keywords: MHD equations; global well-posedness; Lei-Lin space.